Mergers & Acquisitions and the Valuation of Firms. - Wang, Yuan. (2017)
Abstract: Mergers and acquisitions are among the most visible and important phenomena of modern economies worldwide. The great development of information and high technology pushed global M&A activities to hit highest level of the history in both aspects of total deal volume and signal deal value. Firms engaging in M&A pursue economic growth or positive value in every facet of the organization. This work focuses on the trend of firm value with M&A activities. We use enterprise multiple, EV/EBITDA ratio, as measure of firm value and some other financial fundamental ratios as the controls, like price to sale ratio, debt to equity ratio, market to book ratio and financial leverage. We conduct empirical research using a large dataset of 65,000 M&A deals globally from Communication, Technology, Energy and Utility sectors between the years of 2000 to 2010. The econometric models applied to this work are fixed-effect panel regression, Arellano-Bond dynamic panel methodology and treatment effect analysis with propensity score matching, nearest neighborhood matching and regression adjustment. We present the significant contemporaneous effects of the financial fundamental ratios on enterprise multiple, and provide the evidences for long-term and instantaneous impact on firm values pre- and post- M&A activities. The magnitude and significance level of these effects vary cross different company sectors and over different time period.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Economics.; Advisor: Marcelo Bianconi.; Committee: Marcelo Bianconi, Dan Richards, and Gilbert Metcalf.; Keyword: Economics.